Approaches to ensuring the effective implementation of IoT technologies in various industries - Marunich, R.; Sotnik, S. (ХНУРЕ, 2024)
The work discusses current trends and challenges that arise in implementation of IoT technologies in various industries. The key aspects of integration of sensor systems for monitoring, management and optimization of processes in manufacturing, energy, agriculture and other sectors are described. The main constraints faced by enterprises when using such systems are analyzed, including technical, infrastructural and economic aspects. Particular attention is paid to security of data and ensuring its reliable transmission. A systematic approach to overcoming these limitations has been proposed, which contributes to optimization of process of implementing IoT solutions in various sectors of economy. The presented results are of practical value for modernization of existing facilities and development of new monitoring systems.
Keywords: IoT; sensor technology; industrial IoT; sensor integration; condition monitoring; energy efficiency